Navigating the shadows and understanding psychosocial pathways to mental health support among young adults : A Qualitative Study - Joesep, Bermudez; Mary, Harvey; Mae, Garlitoz (Science Center Group, 2025)
Background: Access to mental health services remains a critical public health issue, especially among young adults in urbanizing regions. Structural barriers and sociocultural stigma often hinder timely and appropriate mental health care. This study aimed to explore the barriers and facilitators that influence access to mental health services among young adults with mental health conditions. Methods: A qualitative descriptive design was employed. Sixty participants aged 18–32 years, diagnosed with depression, anxiety, or bipolar disorder, were purposively recruited. Data were collected via WhatsApp chat interviews and Google Forms between September and December 2024. Thematic analysis was used to identify emerging patterns in participants’ experiences. Results: Three major barriers to accessing mental health services were identified: stigma and social silence, limited availability of mental health professionals, and financial constraints. Conversely, three key facilitators emerged: supportive relationships, digital peer communities, and self-awareness. Participants highlighted the role of personal motivation and online networks in bridging formal care gaps, while systemic limitations remained prevalent in local service infrastructure. Findings reveal the dual nature of access to mental health services—where institutional barriers coexist with emerging forms of psychosocial resilience. Conclusion: Strengthening local mental health systems, improving service literacy, and expanding community-based and digital interventions are crucial steps to address mental health disparities among urban youth.